Breket titanium (Titanium bracket) - Sianiwati Goenharto; Achmad Sjafei (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
There has been a considerable discussion in the literature about corrosion and sensitivity to the nickel present in stainless steel brackets. Titanium has been heralded as a material totally compatible in the oral environment and superior in structural integrity compared to stainless steel. Many current applications in dentistry and medicine have made titanium an obvious choice for a possible substitute material. Titanium based brackets have shown excellent corrosion resistance and possessed good biocompatibility. Evaluation of titanium brackets for orthodontic therapy showed that titanium brackets were comparable to stainless steel brackets in passive and active configuration. Study about metallographic structure, hardness, bond strength to enamel substrate, etc. showed that titanium brackets exhibited a potential for clinical application. It was concluded that titanium brackets were suitable substitute for stainless steel brackets.